2020
DOI: 10.3390/ijerph17239027
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Air Pollution and Climatic Factors on Circulatory and Respiratory Mortality in Xi’an, China between 2014 and 2016

Abstract: Several studies have reported that air pollution and climatic factors are major contributors to human morbidity and mortality globally. However, the combined interactive effects of air pollution and climatic factors on human health remain largely unexplored. This study aims to investigate the interactive effects of air pollution and climatic factors on circulatory and respiratory mortality in Xi’an, China. Time-series analysis and the distributed lag non-linear model (DLNM) were employed as the study design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…For many years, the level of air pollution has been associated with several adverse health effects and is among the leading causes of death globally (Mokoena et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the level of air pollution has been associated with several adverse health effects and is among the leading causes of death globally (Mokoena et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even though a mounting body of evidence has suggested the independent impacts of meteorological factors or PM on childhood asthma, limited studies have explored their possible interactive effects to date [22,39,40]. [22]. The results of this study indicate antagonistic interaction between temperature and PM and synergistic interaction between air pressure and PM on the outpatient visits for childhood asthma.…”
Section: Discussionmentioning
confidence: 66%
“…Even though a mounting body of evidence has suggested the independent impacts of meteorological factors or PM on childhood asthma, limited studies have explored their possible interactive effects to date [22,39,40]. [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 16 metropolitan cities in Northeast Asia, a statistically significant interaction between high temperature and air pollutants (PM10, O 3 , CO, NO 2 ) on mortality, with greater synergism effect of PM10 and O 3 on cardiovascular mortality, was found [ 45 ]. In a few Chinese studies, the authors found a synergistic effect of higher temperature with PM2.5 [ 46 , 47 ], PM10 [ 48 ] and O 3 [ 46 ] on circulatory mortality and both the hot and cold effect on PM10 and mortality [ 49 ]. In other parts of Asia, the cold effect on air pollution was observed in Korea (PM2.5) [ 50 ] and Hong Kong (PM10, NO 2 , O 3 ) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%